2022
DOI: 10.1002/smll.202204732
|View full text |Cite
|
Sign up to set email alerts
|

Development of Surface Chemical Strategies for Synthesizing Redox‐Responsive Diatomite Nanoparticles as a Green Platform for On‐Demand Intracellular Release of an Antisense Peptide Nucleic Acid Anticancer Agent

Abstract: Redox‐responsive silica drug delivery systems are synthesized by aeco‐friendly diatomite source to achieve on‐demand release of peptide nucleic acid (PNA) in tumor reducing microenvironment, aiming to inhibit the immune checkpoint programmed cell death 1 receptor/programmed cell death receptor ligand 1 (PD‐1/PD‐L1) in cancer cells. The nanoparticles (NPs) are coated with polyethylene glycol chains as gatekeepers to improve their physicochemical properties and control drug release through the cleavable disulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Various sources of silicon are used in the production of silicates, such as organic silicon, kaolin, and molecular sieves. Among these, diatomite stands out for its safety, cost-effectiveness, and environmentally friendly attributes, effectively addressing the limitations arising from the synthesis of composites [142]. Up to now, the use of diatomite as a raw material has led to the creation of various types of silicates [143,144].…”
Section: Diatomite As a Silicon Source For Silicatesmentioning
confidence: 99%
“…Various sources of silicon are used in the production of silicates, such as organic silicon, kaolin, and molecular sieves. Among these, diatomite stands out for its safety, cost-effectiveness, and environmentally friendly attributes, effectively addressing the limitations arising from the synthesis of composites [142]. Up to now, the use of diatomite as a raw material has led to the creation of various types of silicates [143,144].…”
Section: Diatomite As a Silicon Source For Silicatesmentioning
confidence: 99%
“…Unfortunately, PNAs show limited tissue accessibility, low water solubility, and an unfavorable pharmacokinetic profile, hindering their translation into clinics [ 103 ]. Terracciano et al recently reported redox-responsive DNPs loaded with an anti-PD-L1 PNA for enhanced uptake in cancer cells and efficient protein downregulation [ 59 ] ( Table 1 ). The PNA was bound to polyethylene glycol (PEG)-modified DNPs via a disulfide bond with a loading efficiency of 31% and released after bond reduction by glutathione in cancer cells.…”
Section: Standardized and Groundbreaking Approaches To Fight Against ...mentioning
confidence: 99%
“…Due to the excess of glutathione in the tumor (2–20 mM) compared to normal tissues, the strategy shown by Terracciano et al promoted PNA release in malignant cells with higher efficiency than in healthy samples, reducing off-target protein downregulation and toxicity. Moreover, DNPs improved the uptake of PNA in A549 cells already after 6 h of incubation ( Figure 6 a), yielding an internalization four-fold higher than the free PNA [ 59 ]. Managò et al used Raman spectroscopy to determine the kinetics of internalization and localization of siRNA-loaded DNPs with an average diameter of 450 nm targeting cancer cells [ 104 ].…”
Section: Standardized and Groundbreaking Approaches To Fight Against ...mentioning
confidence: 99%
“…14 However, despite the remarkable potentialities possessed by PNAs, their poor water solubility, low uptake by eukaryotic cells, and rapid renal clearance have so far prevented the application of PNAs in the biomedical field. To overcome these limitations several strategies have been considered 15 even though the cellular uptake remains an unsolved issue and there are currently no drugs available based on PNA, even though a recent publication mentions one PNA drug in clinical trials, and others in development. 16 Recently, some of us reported the covalent linkage of PNA tetramers, chosen as a model, to HNTs to develop nanomaterials for intracellular PNA delivery.…”
Section: Introductionmentioning
confidence: 99%